Performance of Two-Hop DS-CDMA Systems Using Amplify-and-Forward Protocol over Different Fading Channels - Kapucu, Nuri; Bilim, Mehmet; Develi, Ibrahim (Elektronika ir Elektrotechnika, 2016)
This study analyses the performance of direct-sequence code division multiple access (DS-CDMA) based on two-hop amplify-and-forward protocol over Weibull symmetric fading channels as well as Rayleigh/Rician, Rician/Rayleigh asymmetric fading phenomenas. We investigate the bit-error rate (BER) of the considered system using multiple relays by considering the effect of Weibull fading parameter and Rician K factor on the system performance. Our simulation results demonstrate the positive impacts of the value of fading parameter, Rician K factor and increasing number of relay nodes on BER performance. It is also confirmed that the Rician K factor is more effective on the system performance over Rician/Rayleigh fading channels in comparison with Rayleigh/Rician fading environment. DOI: http://dx.doi.org/10.5755/j01.eee.22.1.14116